2023
DOI: 10.4049/jimmunol.2200337
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Effector TCR Avidity for Peptide on APC Determines the Level of Memory Generated

Abstract: Initial TCR affinity for peptide Ag is known to impact the generation of memory; however, its contributions later, when effectors must again recognize Ag at 5–8 d postinfection to become memory, is unclear. We examined whether the effector TCR affinity for peptide at this “effector checkpoint” dictates the extent of memory and degree of protection against rechallenge. We made an influenza A virus nucleoprotein (NP)-specific TCR transgenic mouse strain, FluNP, and generated NP-peptide variants that are presente… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Moreover, the impact of avidity on responding effectors was already apparent in their survival after only 3 dpi and was also proportional to the amount of IL-2 produced by the responding effectors, which was strictly driven by avidity and peptide dose. This supports the concept that autocrine IL-2 acts directly to support effector survival and explains how the strength of TCR signals determines the extent of CD4 memory generation ( 21 ).…”
Section: Background and Recent Studiessupporting
confidence: 79%
See 4 more Smart Citations
“…Moreover, the impact of avidity on responding effectors was already apparent in their survival after only 3 dpi and was also proportional to the amount of IL-2 produced by the responding effectors, which was strictly driven by avidity and peptide dose. This supports the concept that autocrine IL-2 acts directly to support effector survival and explains how the strength of TCR signals determines the extent of CD4 memory generation ( 21 ).…”
Section: Background and Recent Studiessupporting
confidence: 79%
“…We pulsed activated APC with high concentrations of each peptide to evaluate the impact of avidity on NP-specific CD4 T cells. We found that higher TCR avidity for peptide-MHC-II proportionally increased memory generation ( 21 ). Moreover, the impact of avidity on responding effectors was already apparent in their survival after only 3 dpi and was also proportional to the amount of IL-2 produced by the responding effectors, which was strictly driven by avidity and peptide dose.…”
Section: Background and Recent Studiesmentioning
confidence: 88%
See 3 more Smart Citations